KARAKTERISASI MORFOLOGI VARIETAS JAGUNG KETAN DI KECAMATAN ULUBONGKA KABUPATEN TOJO UNA-UNA - Yusran, Yusran; Maemunah, Maemunah (MEDIA LITBANG SULTENG, 2011)
The research aiming to invent, characterize, and identify the character varieties of cultivar cluster of glutinous maize at Mire, Watusongu, and Paranonge Villages of Ulubongka Subdistric Tojo Una-una Residence was conducted in January to March 2010.Â The research employs survey and observation where sample locations is based on information taken from Agriculture, Estate,Â  Animal Husbandry and Animal Healthy Agencies of Tojo Una-una Regency. Observation was focused on morphological characters such as plant weight, stem diameter, length and width of leaf flowering time, knob length, knob circle with and without seeds, length of stem stalk, number of seed per knob, number of seed rows per knob, number of seeds per row, length of seed row per knob, seed weight per knob, knob weight, weight of knob without seed, weight of 100 seeds, and number of seed colour. Cluster analysis was done further using SYSTAT 8,0 Software Program. The result shows that based on sub regency dendrogram there are six cultivar groups with genetic relationship, of each was represented by PR01 and PR04 from Paranonge Village, MR04, MR05 and MR01 from Mire Village, and WT04 from Watusongu Village as chosen cultivars at Ulubongka Subdistrict